Stock market economics - Rix, Margaret Shelley (London : Pitman, 1963)
The work is divided into three main parts. The first, from Chapters 1 to VII, describes and comments upon the functions and organization of the London Stock Exchange, the attitude of borrowers, and the importance of investors and of the role they play in our economic life. The second part comments, in Chapter VIII, on the more important statistical information on marketable securities. The third part of the book discusses investment principles.
osc 24/07/2018
Loans
Keywords: Stock exchanges; Securities